2019
DOI: 10.4103/jfmpc.jfmpc_57_19
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical outcomes of acute glomerulonephritis in a teaching hospital in North India

Abstract: Context: Acute glomerulonephritis (AGN) is a major cause of morbidity in developing countries like India. AGN includes both infectious and non infectious causes leading to immunological insult to the kidney. Aims: This study is an attempt to evaluate the clinical characteristics, complications and outcome of acute glomerulonephritis. Settings and Design: This hospital based descriptive study was conducted at a tertiary care hospital in North … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
4
5
0
2
Order By: Relevance
“…Acute post-infectious glomerulonephritis (APIGN) is common in age group of 5-14 year age, predominantly in males with ratio of 1.86:1.3, and is very rare with <5% below 2 years of age while, in the present study the youngest one was 1 year old and the children below 5 years of age is about 19.02%. 6 - 8 , 12 - 14 These observations were in accordance with the other studies. 7 , 12 - 14 Glomerulonephritis is least common in very early age may be due to immature immune response in early age.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Acute post-infectious glomerulonephritis (APIGN) is common in age group of 5-14 year age, predominantly in males with ratio of 1.86:1.3, and is very rare with <5% below 2 years of age while, in the present study the youngest one was 1 year old and the children below 5 years of age is about 19.02%. 6 - 8 , 12 - 14 These observations were in accordance with the other studies. 7 , 12 - 14 Glomerulonephritis is least common in very early age may be due to immature immune response in early age.…”
Section: Discussionsupporting
confidence: 93%
“… 11 , 15 Despite the higher incidence of cardiac complications in our study, there was no mortality, similar to other studies. 6 , 8 , 14 This may be because of early presentation in the hospital, timely management and well control of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study 12 out of 30 children had atypical presentations which is similar to studies done by Kuralvanan Gunasekaran et al (9) and Islam Bhuiyan et al (10). Kapil Bhalla et al (1) showed higher incidence of Acute kidney injury and congestive cardiac failure in children with AGN.…”
Section: Table -2: Clinical Featuressupporting
confidence: 90%
“…приходится на детский возраст [13]. По результатам недавно проведенного исследования отмечается увеличение заболеваемости ОГН среди детей с неблагоприятным социальным статусом [14]. В исследовании M. Sharmin, et al (2020) были изучены социально-демографические особенности клинического профиля и исходов ОГН у госпитализированных детей, живущих в сельской местности [15].…”
Section: этиопатогенез и морфологические измененияunclassified